Neoliberal Timescapes of Infrastructuring an Environmental Footprint: Configuring Carbon Emissions as Flexibly Substitutable Placeholders - Ingmar Lippert (Tecnoscienza)
Environmental discourses shift over time. Corporations are interested in maintaining efficient systems that translate their operation’s environmental impacts into specific environmental discourses, such as carbon. For this purpose, corporate environmental management systems employ accounting. In accounting apparatuses material environmental relations are represented digitally. I attend to maintainers of such digital infrastructures and analyse how they enact the corporation’s environmental relations as sufficiently stable. I show that achieving such stability over time is indeed a critical project because the socio-technical relations of the infrastructure routinely threaten such stability. To devise a time-sensitive infrastructural analysis, this problematisation adopts Barbara Adam’s timescapes perspective and Lucy Suchman’s concept of configuration. Annelise Riles’ notion of the placeholder supports theorising the specific political quality of the infrastructural relations. I draw on ethnographic research into corporate carbon accounting in a transnational company. The empirical material consists of an ethnographic story composed of key artefacts of the accounting infrastructure and participant observation of situated engagements with these artefacts by the environmental managers; specifically, I address situations in which participants enact too swift emission reduction, the synchronisation of emissions and the versioning of environments. This story powers detailing how time is imagined and inscribed in critical infrastructural relations. Across these analyses, I problematise how the managers of these corporate carbon emissions continuously (re)configure the latter into an appropriately flexible environmental reality. In sum, I argue that complex temporal politics are at work within maintaining emissions in the corporation to produce tailored versions of environmental realities, effecting a neoliberal timescape.